Coping or adapting strategies? The importance of distinguishing between climatic shift and drought events for proper management of the pastoral systems in Northern Patagonia - Hurtado, Santiago Ignacio; Michel, Carolina Lara; Fernandez, Manuela Teresa; Calianno, Martin; Easdale, Marcos Horacio (Springer, 2024)
Drier conditions have been observed in Northern Patagonia, Argentina, in the last decades, affecting the pastoralism production system. In this context, two laws were promoted to foster goat and sheep production. This research investigated the hydro-climatic changes and the governmental initiatives, within these two laws, that follow them with special emphasis on climate hazard responses and their relationship with coping or adaptation strategies. A climatic shift was found as a tipping point in the climatic regime to drier conditions in 2006/7. This is observed in the annual mean streamflow of the Neuquén river which presented a 40% drop. Governmental funds were mostly oriented to tackle water-bonded problems given the lack of water and the remaining budget was mainly destined to infrastructure. This was done under the belief of drought events rather than a climatic shift. Distinguishing between them is a key factor for risk management stakeholders, since a drought must be mitigated with coping strategies, whereas a climate shift implies a long-lasting adaptation to a new reality. Even though they were not initially designed with consideration for climate change, some of these measures favor the adaptation process to this new drier scenario. Thus, many of the measures aimed to mitigate the structural vulnerabilities of the pastoral system in the region. This new scenario has triggered the need for a compulsory broad change in the socio-productive pastoral system, which might take more time than the assimilation of the negative impacts.